Accountability Practices of Village Owned Enterprises (BUM Desa) - Andi Laksono; Puji Handayati; Agung Winarno (International Journal of Accounting and Finance in Asia Pasific (IJAFAP), 2023)
The BUM Desa organizational apparatus is required to carry out its duties and authorities in a professional, efficient and effective manner, as well as accountable. Accountability is the obligation to provide information including financial information as a form of organizational responsibility. This study aims to analyze the financial accountability practices of BUM Desa Ageng using indicators of financial integrity, disclosure and compliance with laws and regulations. The management of BUM Desa Ageng has good integrity by upholding the values of honesty and ethics, even though the organization runs without SOPs. The financial disclosure of BUM Desa Ageng has not been able to fulfill the preparation of 5 reports according to SAK ETAP. The process of establishing BUM Desa Ageng has implemented accountability practices in the aspect of compliance with laws and regulations, although it still involves village officials as operational implementers of BUM Desa.